An improved soft-switching single-phase inverter for small grid-connected PV-system - Damrong Amorndechaphon (2018)
In order to increase the conversion efficiency of grid-connected PV-systems, a high-efficiency PV power inverter with simple control methodology is required. To satisfy this requirement, an improved single-phase inverter using softswitching technique is proposed. The proposed power inverter circuit is composed of a ZVT-PWM boost dc-dc converter and a LLCC resonant inverter. The dc-link voltage amplitude is controlled by ZVT-PWM boost dc-dc converter with softswitching transition for all active switches. The stable sinusoid ac output voltage is inverted from dc-link voltage via a LLCC resonant inverter. The effectiveness of the proposed gridconnected inverter for small PV system is verified by simulation results. © 2008 IEEE.